Electromagnetic Compatibility Problems in LTE Mobile Networks 800 MHz Frequency Band - Stankevicius, Evaldas; Medeisis, Arturas; Paulikas, Sarunas; Anskaitis, Aurimas (Elektronika ir Elektrotechnika, 2015)
This paper examines the LTE UE (Long-Term Evolution User Equipment) in 800 MHz frequency band (the so-called digital dividend) interference to Short Range Devices (SRD) in the band of 863 MHz–870 MHz. The fundamental objective of this research is to evaluate the probability of interference and influence of LTE UE emission mask in this regards. The study was performed in two methods: theoretical – simulations with SEAMCAT software and practical – measurements to verify gathered results in simulations. The results of this paper characterize the required technical conditions for LTE mobile networks deployment in 800 MHz band. DOI: http://dx.doi.org/10.5755/j01.eee.21.6.13770